Analysis Of Raw Material Inventory Control Using The Economic Order Quantity (EOQ) Method To Avoid Overstock In The Kotin Tempe Home Industry - Chintia Novrianti; Isnaini Harahap; Saparuddin Siregar (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This research examines how soybean raw material inventory is control at Kotin Tempe Home Industry by implementing the Economic Order Quantity (EOQ) approach to prevent excessive stockpiling and enhance cost effectiveness. Employing a quantitative descriptive methodology that includes observation and interviews, findings reveal that the current inventory management lacks proper structure, with 48 annual orders made without maintaining safety reserves or establishing reorder thresholds. When the EOQ approach is applied, optimal procurement amounts to 350 kg ordered 14 times annually, with safety reserves of 62 kg (2023) and 45 kg (2024), and reorder thresholds set at 89 kg and 72 kg respectively. This approach achieves a 65% reduction in inventory expenses, equivalent to Rp1,300,000 annually, demonstrating how EOQ effectively lowers costs and reduces overstock risks. This study is expected to be able to help this business determine the most appropriate amount of soybean raw material orders to achieve optimal profits.